COMPARISON BETWEEN TWO PERFORMANCE CALCULATION METHODS APPLIED FOR VAWT - Goucem, Mahdi; Senouci, Mahi; Imine, Omar (Journal of Applied Engineering Science, 2022)
This paper presents a new model of 2D performance calculation applied to VAWT. The idea consist in considering only one blade to which a rotational oscillation motion is gave. Hence, the effect of the machine rotation and the influence of the rest of the machine on the focused blade are modelled. The study is purely numerical based upon the use of ANSYS- Fluent code to solve unsteady RANS equations, which follow from the new model. Several 2D geometry configurations of Darrieus machine were tested using the new approach and the results are compared to ones applied to the whole 2D rotor. A quasi concordance of the results is noticed for the overall predictions done from the two CFD methods. Although computational time is lower for the new model, tests reveal inadequate prediction of the peak’s power coefficient and its Tip Speed Ratio value.